1,4-Dioxane as an emerging water contaminant: State of the science and evaluation of research needs - Godri Pollitt, Krystal J.; Kim, Jae-Hong; Peccia, Jordan; Elimelech, Menachem; Zhang, Yawei; Charkoftaki, Georgia; Hodges, Brenna; Zucker, Ines; Huang, Huang; Deziel, Nicole C.; Murphy, Kara; Ishii, Momoko; et al. (The Science of the total environment, 2019)
1,4-Dioxane has historically been used to stabilize chlorinated solvents and more recently has been found as a contaminant of numerous consumer and food products. Once discharged into the environment, its physical and chemical characteristics facilitate migration in groundwater, resulting in widespread contamination of drinking water supplies. Over one-fifth of U.S. public drinking water supplies contain detectable levels of 1,4-dioxane. Remediation efforts using common adsorption and membrane filtration techniques have been ineffective, highlighting the need for alternative removal approaches. While the data evaluating human exposure and health effects are limited, animal studies have shown chronic exposure to cause carcinogenic responses in the liver across multiple species and routes of exposure. Based on this experimental evidence, the U.S. Environmental Protection Agency has listed 1,4-dioxane as a high priority chemical and classified it as a probable human carcinogen. Despite these health concerns, there are no federal or state maximum contaminant levels for 1,4-dioxane. Effective public health policy for this emerging contaminant requires additional information about human health effects, chemical interactions, environmental fate, analytical detection, and treatment technologies. This review highlights the current state of knowledge, key uncertainties, and data needs for future research on 1,4-dioxane. [Display omitted] •1,4-Dioxane is an emerging environmental contaminant and a probable carcinogen.•The de minimis cancer risk level is exceeded at 7% of U.S. drinking water sites.•The physicochemical properties challenge detection and remediation of 1,4-dioxane.•This review presents data needed to set an enforceable drinking water standard.